2018
DOI: 10.1080/02626667.2018.1538593
|View full text |Cite
|
Sign up to set email alerts
|

Identifying advantages and drawbacks of two hydrological models based on a sensitivity analysis: a study in two Chilean watersheds

Abstract: Hydrological modelling has undergone constant growth with the increase in information processing capabilities. Hydrological models have traditionally been used to study the effects of climate change on management and land-use changes and for water resources planning, among other purposes. The aim of this study was to determine and analyse the advantages of the HBV and HYMOD models, which are commonly used in hydrology on daily and monthly time scales. A regional sensitivity analysis was used to compare the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…The HBV model and its various versions have been applied in a range of watersheds and climates and several countries [49], including Belgium [50], Sweden [51,52], China [53], and the United States [54], serving as a suitable alternative for flow estimation in a variety of watershed types. Moreover, it has been used at different time scales (e.g., Parra et al [55]), where the obtained results support the model performance and its ability to adequately represent the main hydrological processes.…”
Section: Hydrological Model and Methodsmentioning
confidence: 65%
“…The HBV model and its various versions have been applied in a range of watersheds and climates and several countries [49], including Belgium [50], Sweden [51,52], China [53], and the United States [54], serving as a suitable alternative for flow estimation in a variety of watershed types. Moreover, it has been used at different time scales (e.g., Parra et al [55]), where the obtained results support the model performance and its ability to adequately represent the main hydrological processes.…”
Section: Hydrological Model and Methodsmentioning
confidence: 65%
“…In this context, payments for ecosystem services (PES) can be a suitable mid-to long-term solution to provide soil and water conservation, guarantee forest restoration and river flow rate regulation, and improve water quality (Pagiola et al, 2007;Rodríguez Osuna et al, 2014;Zolin et al, 2014). The use of soil and water conservation approaches in watersheds have been shown to be valuable, in the context of water production, as reported by Pires (2004) and Sone et al (2019).…”
Section: Planning For Resiliencementioning
confidence: 99%
“…To analyze the performance of the models the LOGNSE function (described in the following section), which focused on the simulation of low flows, was used. Table 2 presents the calibration parameter ranges defined in accord with the conceptual representation of each and experience acquired in a prior study on Chilean watersheds [9]. Considering that at the Andes mountain range there was a low density of rain gauges because most were located in low-altitude areas, consequently, the spatial distribution of precipitation was not properly recorded [36].…”
Section: Analyzed Groundwater Storage Structuresmentioning
confidence: 99%
“…Meanwhile, conceptual models have the advantage of requiring a lower quantity of input data (e.g., precipitation, temperature), but generate a simplified representation of the physical processes that occur in a watershed. Nonetheless, various recent investigations have shown that conceptual models can provide reliable models (e.g., Skaugen et al [6]; Toledo et al [7]; Muñoz et al [8]; Parra et al [9]); therefore, a conceptual model is a reliable alternative for studying hydrological processes in watersheds with limited hydrological information.…”
Section: Introductionmentioning
confidence: 99%